Parameter optimization of 3D models of centrifugal juicer with auto-balancer by minimization of steady vibroacceleration - Филимонихин, Геннадий Борисович; Гончаров, Валерий Владимирович (Eastern-European Journal of Enterprise Technologies, 2014)
During the operation of electrical centrifugal juicers (Juicer) with cylindrical filter-sieve (sieve) a depressed weight is unevenly distributed over the sieve, which causing imbalance and vibration of the juicer. In this paper in order to find the optimal parameters of the auto-balancer the technique, which takes into account the peculiarities of rotary machines with auto-balancer and using the theory of multivariate experiment, was proposed. It includes: - the process of drafting the "black" box (choice of the objective function, the choice of control factors and their fields of changes in the dimensionless form); - planning multifactorial experiment; - research of the obtained results using programs STATISTICA_6 and MathCad (three regression models between the objective function and factors - linear, taking into account the effects of the mutual influence of the first order, quadratic, were investigated). As a result, studies have shown that: - auto-balancer reduces vibration acceleration on average 8.4-9.2 times; - linear and quadratic models are effective in approximation, they give similar optimal points, but a linear function is less accurate in predicting the minimum steady acceleration. The described technique can be considered as a standard in the optimization of parameters of auto-balancer in the rotor system.